2022
DOI: 10.3389/fpls.2022.965345
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin treatment improves postharvest quality and regulates reactive oxygen species metabolism in “Feizixiao” litchi based on principal component analysis

Abstract: Postharvest quality of litchi reduces rapidly during storage at room temperature. This study aimed to investigate the effect of melatonin treatment on postharvest quality and oxidative stress markers of litchi fruit during cold storage. The “Feizixiao” litchi was treated with melatonin solution concentrations of 0.2 and 0.6 mmol·L−1 and then stored at 4°C for 12 days. The results confirmed that the melatonin treatment effectively maintained the appearance and color of the litchi fruit, suppressed the peel brow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…Principal component analysis has been widely used to analyze a variety of horticultural crops, including guava, peach and blueberry [ 51 , 52 , 53 ]. The effect of melatonin treatment on postharvest quality and oxidative stress markers of litchi fruit during cold storage was determined using PCA as well as correlation analysis, showing that melatonin treatment effectively delayed the fruit senescence by enhancing the antioxidant enzyme activities and modulating peel browning [ 54 ]. Paulina et al [ 55 ] identified the most important variables in the relationship between 20 selected peach varieties based on PCA model and identified the most attractive varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis has been widely used to analyze a variety of horticultural crops, including guava, peach and blueberry [ 51 , 52 , 53 ]. The effect of melatonin treatment on postharvest quality and oxidative stress markers of litchi fruit during cold storage was determined using PCA as well as correlation analysis, showing that melatonin treatment effectively delayed the fruit senescence by enhancing the antioxidant enzyme activities and modulating peel browning [ 54 ]. Paulina et al [ 55 ] identified the most important variables in the relationship between 20 selected peach varieties based on PCA model and identified the most attractive varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al [12] found that MT-treated fruits that were exposed under chilled conditions for a prolonged period significantly enhanced the AsA content and thus controlled the ROS-induced membrane degradations. Xie et al [41] reported that MT could regulate the ROS metabolism and modulate the antioxidant genes, thereby reducing oxidative stress and maintaining overall fruit quality. These findings are in accordance with the present study, where the application of MT could be able to control the ROS and increase NEA.…”
Section: El Ros and Mdamentioning
confidence: 99%
“…High MT concentrations (>50 µmol L −1 ) more effectively controlled LOX activity than lower concentrations. Studies have reported that MT treatment could adversely affect the production of MDA and H 2 O 2 by enhancing the AO enzyme activities and thus effectively controlling the PLD and LOX activities in the plants [21,41]. Kong et al [11] found that the application of MT on the pepper fruit significantly controlled the production of MDA and suppressed the PLD and LOX activity by inhibiting their specific gene expressions.…”
Section: Enzyme Activitiesmentioning
confidence: 99%
“…Meanwhile, the accumulation of ROS during postharvest accelerates fruit softening, senescence, and browning, thereby worsening fruit quality and hastening the senescence process ( Adiletta et al., 2021 ). Multiple studies have demonstrated that the boost in ROS scavenging ability induced by postharvest exogenous treatments effectively delays fruit deterioration and postharvest senescence ( Xie et al., 2022 ). Exogenous melatonin treatment increases the activities of super-oxide dismutase (SOD), peroxidase (POD), and catalase (CAT), as well as the buildup of ascorbate and total phenol, thus maintaining the fruit quality of ‘Newhall’ navel orange during postharvest ( Ma et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%